Conserved genetic pathways associated with microphthalmia, anophthalmia, and coloboma. Issue 2 (3rd June 2015) - Reis, Linda M.; Semina, Elena V.
<x xml:space="preserve">Abstract</x> The human eye is a complex organ whose development requires extraordinary coordination of developmental processes. The conservation of ocular developmental steps in vertebrates suggests possible common genetic mechanisms. Genetic diseases involving the eye represent a leading cause of blindness in children and adults. During the last decades, there has been an exponential increase in genetic studies of ocular disorders. In this review, we summarize current success in identification of genes responsible for microphthalmia, anophthalmia, and coloboma (MAC) phenotypes, which are associated with early defects in embryonic eye development. Studies in animal models for the orthologous genes identified overlapping phenotypes for most factors, confirming the conservation of their function in vertebrate development. These animal models allow for further investigation of the mechanisms of MAC, integration of various identified genes into common developmental pathways and finally, provide an avenue for the development and testing of therapeutic interventions. Birth Defects Research (Part C) 105:96–113, 2015. © 2015 Wiley Periodicals, Inc.